Bandgap Engineering of Lead‐Halide Perovskite‐Type Ferroelectrics. Issue 13 (2nd February 2016) - Ye, Heng‐Yun; Liao, Wei‐Qiang; Hu, Chun‐Li; Zhang, Yi; You, Yu‐Meng; Mao, Jiang‐Gao; Li, Peng‐Fei; Xiong, Ren‐Gen
Abstract : Semiconducting ferroelectricity is realized in hybrid perovskite‐type compounds (cyclohexylammonium)2 PbBr4−4 x I4 x ( x = 0–1). By adjusting the composition x, the bandgap is successfully tuned from previously reported 3.65 eV to as low as 2.74 eV, and the excellent ferroelectricity was kept intact. This finding may contribute to improving the photoelectronic and/or photovoltaic performance of hybrid perovskite‐type compounds.